2017
DOI: 10.1007/s12253-017-0223-5
|View full text |Cite
|
Sign up to set email alerts
|

COL1A2 is a Novel Biomarker to Improve Clinical Prediction in Human Gastric Cancer: Integrating Bioinformatics and Meta-Analysis

Abstract: Gastric cancer is the third most common cause of cancer-related death in worldwide. It is crucial to target the key genes controlling pathogenesis in the early stage of gastric cancer. This study describes an integrated bioinformatics to identify molecular biomarkers for gastric cancer in patients' cancer tissues. We reports differently expression genes in large gastric cancer cohorts from Gene Expression Ominus (GEO). Our findings revealed that 433 genes were significantly different expressed in human gastric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 20 publications
2
37
0
Order By: Relevance
“…Collagen type I alpha 2 (COL1A2), which encodes the pro‐alpha 2 chain of type I collagen, is a key gene in a 37‐gene network that modulates cell motility through interaction with the cytoskeleton . It is noted that COL1A2 is differentially expressed in gastric cancer by complementary DNA (cDNA) microarray .…”
Section: Introductionmentioning
confidence: 99%
“…Collagen type I alpha 2 (COL1A2), which encodes the pro‐alpha 2 chain of type I collagen, is a key gene in a 37‐gene network that modulates cell motility through interaction with the cytoskeleton . It is noted that COL1A2 is differentially expressed in gastric cancer by complementary DNA (cDNA) microarray .…”
Section: Introductionmentioning
confidence: 99%
“…A link with the presence of bone marrow-derived fibrocyte-like cells, defined as α-1 type I collagen-positive cells producing FGF2, has also been reported in human malignant mesothelioma (98). More recently, Rong et al demonstrated that the collagen type I alpha 2 chain (COL1A2) gene modulated cell motility through interaction with the cytoskeleton (99).…”
Section: Cathepsin D and Transglutaminase 2 (Tgm2)mentioning
confidence: 88%
“…Previous studies have reported some of these genes. For example, Rong et al (2018) have reported high expression of COL1A2 in GC tissues, which was significantly correlated to the histological type and the lymph node status. Li, Ding & Li (2016) hypothesized a diagnostic use of COL1A1 to screen for early GC.…”
Section: Discussionmentioning
confidence: 99%